MEMS and EFF Technology based micro connector for future miniature devices - Bhuiyan, Md. Moinul Islam; Rashid, Muhammad Mahbubur; Alamgir, Tarik Bin; Bhuiyan, Munira; Kajihara, Masanori (2013)
The development of a miniature; size, light and high performance electronic devices; has been accelerated for further development. In commercial stamping method, connector pitch size (radius) is more than 300μm due to its size limitation. Therefore, the stamped contact hertz stress becomes lower and less suitable for fine pitch connector. To overcome this pitch size problem a narrow pitch Board-to-Board (BtoB) interface connectors are in demand for the current commercial design. Therefore, this paper describes a fork type micro connector design with high Hertz-Stress using MEMS and Electro Fine Forming (EFF) fabrication techniques. The connector is designed high aspect ratio and high-density packaging using UV thick resist and electroforming. In this study a newly fabricated micro connector’s maximum aspect ratio is 50μm and pitch is 80μm is designed successfully which is most compact fork-type connector in the world. When these connectors are connected, a contact resistance of less than 50mΩ has been attained by using four-point probe technique.